2021 Newfoundland and Labrador Election Study - Stephenson, Laura B.; Harell, Allison (Borealis, 2023)
This election study survey is based upon questions asked in the Canadian Election Study, but tailored for the Newfoundland and Labrador context. It was conducted by the Consortium on Electoral Democracy (C-Dem).